Pengaruh Lingkungan Kerja dan Burnout terhadap Kinerja Karyawan PT. Nusantara Batulicin Kabupaten Tanah Bumbu - Mursanto, Mursanto; MS, Abdul Kadir (Innovative: Journal Of Social Science Research, 2024)
This research is used to find out or test how much influence the work environment partially has on employee performance, then to find out how much partial influence Burnout has on employee performance and finally to find out and test how much influence the work environment and Burnout simultaneously have on employee performance. at PT Nusantara Batulicin, Tanah Bumbu Regency. This research design uses quantitative research, namely scientific research that systematically uses numbers and statistics in the collection and analysis of measured and measurable data, using 30 respondents using analysis and multiple linear regression. Then the results of this research show that: 1). The work environment has a significant influence on employee performance, 2) Burnout also has a significant influence on employee performance, and 3) The work environment and Burnout simultaneously influence employee performance. This identifies that work environment factors and burnout such as physical and mental fatigue at work have a huge influence on employee performance, therefore the company, in this case PT Nusantara Batulicin, Tanah Bumbu Regency, really pays attention to its employees as company assets.